Investigating the Potential of an In-Situ Method for Monitoring the Malting of Barley Using Solid Phase Microextraction with a Portable Gas Chromatography Mass Spectrometry Instrument - Mark D. Hodges; Neil Fitzgerald (Beverages, 2020)
An improved understanding of the malting process could have a significant impact on the efficient production of quality malt for the brewing industry. Analysis of volatile organic compounds produced during the malting process is one approach towards achieving this goal. In-situ methods avoid the possibility of contamination and chemical changes occurring during sample transport and storage. This paper describes the investigation of an in-situ sampling method for the detection of volatile organic compounds produced during the malting of barley. Solid Phase Microextraction Gas Chromatography Mass Spectrometry (SPME-GC/MS) was used to identify compounds. The investigated method involved the direct exposure of an SPME fiber in the kiln during barley malting. Using this method, compounds including aldehydes, ketones, and esters were detected. Some changes in volatile organic compound composition were observed during the production of pale malt at a commercial malting house.